2005
DOI: 10.1111/j.1550-7408.2005.04-3273.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of Encystation and Excystation in Acanthamoeba castellanii

Abstract: Encystation and excystation of Acanthamoeba castellanii were studied by transmission electron microscopy. The differentiation process was induced in asynchronous cultures grown axenically. Cytoplasmic vesicles containing a dense fibrous material very similar in appearance to the cyst wall were observed in trophozoites induced to encyst. When these trophozoites were incubated with calcofluor white m2r, fluorescence was observed in cytoplasmic vesicles, suggesting that the material contained in these vesicles co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 20 publications
9
54
0
Order By: Relevance
“…The observed differences in resistance may partly be due to the ectocyst structure, since it was significantly (P Ͻ 0.001) thicker in the more resistant strain than in the others. This cyst wall structure has been demonstrated to contain large amounts of cellulose (15), and an increase in cyst wall cellulose content during encystment has been demonstrated to coincide with increasing resistance to biocides (60). Other mechanisms may also play a role, since the cysts of strain 4 presented a thickness similar to those of strain 1 but were significantly (P Ͻ 0.001) more resistant to treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences in resistance may partly be due to the ectocyst structure, since it was significantly (P Ͻ 0.001) thicker in the more resistant strain than in the others. This cyst wall structure has been demonstrated to contain large amounts of cellulose (15), and an increase in cyst wall cellulose content during encystment has been demonstrated to coincide with increasing resistance to biocides (60). Other mechanisms may also play a role, since the cysts of strain 4 presented a thickness similar to those of strain 1 but were significantly (P Ͻ 0.001) more resistant to treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Dictyostelium is almost certainly derived from ancestors that were solitary in both proliferative and developmental stages. Solitary Amebozoans generally encyst when starved, and these cysts may resemble Dictyostelium spores in function (Mazur et al, 1995) and in aspects of morphology (Chavez-Munguia et al, 2005). It thus seems likely that encystment in the non-social ancestors of Dictyostelium involved an Rb-family gene.…”
Section: Dictyostelium Retinoblastoma and Evolutionmentioning
confidence: 99%
“…Chávez-Munguía et al suggest that cellulose is present in both layers of the cyst wall (9), while previous studies proposed that cellulose is present only in the endocyst (30,66). Recently, it has been shown that the ectocyst presented an irregular surface and that vesicles were found within its wall.…”
Section: Cyst Wall Morphology Of Flamentioning
confidence: 99%
“…These layers are composed of at least acid-insoluble proteins (45) and cellulose (62), but the exact composition is not well known. The structure of Acanthamoeba cysts has been well described by electron microscopy (5,9). One to several holes named ostioles are present at the surface of the cyst wall.…”
Section: Cyst Wall Morphology Of Flamentioning
confidence: 99%
See 1 more Smart Citation